Factors affecting transport-related social exclusion: territorial classification of Czechia - Jaroš, Václav; Marada, Miroslav (Bulletin of Geography. Socio-economic Series, 2025)
Manifestations of social disparities take different forms and have various causes. In extreme cases, they lead to social exclusion. On the one hand, transport is an instrument for excluded individuals to participate in society. But on the other, where there is a lack of mobility and accessibility options, transport itself becomes a factor on which social exclusion is based. This study assesses objective and subjective factors regarding transport-related social exclusion. In the case of Czechia, a classification of the lowest territorial units of the state is elaborated in terms of the type of transport exclusion to which their inhabitants are potentially exposed. This example proves that the various characteristics of the settlement system in particular result in the potential for the emergence of different types of transport disadvantages. It is the task of the whole of society to find an adequate tool in response, to ensure transport inclusion.